CHARACTERISTICS OF DISEASE SYMPTOMS EXPERIENCED BY COMMUNITIES AROUND MINE SITES AND GEOTHERMAL MANIFESTATION AREAS IN DRIEN MANGKO VILLAGE, WOYLA DISTRICT, ACEH BARAT DISTRICT - Wahyuni, Srie; Lensoni, Lensoni; Meilisa, Rima (PHARMACOLOGY, MEDICAL REPORTS, ORTHOPEDIC, AND ILLNESS DETAILS, 2023)
According to WHO, mercury is a metallic element that occurs naturally and is classified into 3 main groups, namely liquid and gas, inorganic mercury such as mercury chloride, mercury acetate, mercury sulfide, and organic mercury. The research was conducted in November involving 32 respondents from gold mining communities and the research location was in Drien Mangko Village, Woyla District, West Aceh Regency. Samples were taken from communities around gold mining in the gold mining area and around the mine. Sample measurement by providing a prepared questionnaire. The results of the research showed that the acute clinical symptoms of the community were that the majority of respondents experienced symptoms of headache and swelling of the salivary glands (18 respondents), vomiting (14 respondents), chest tightness and bloody urine (12 respondents), numbness in the mouth (10 respondents), loose teeth. easy to fall out (9 respondents), difficulty breathing (8 respondents), pelvic pain (6 respondents), nausea (5 respondents), loss of sense of smell (2 respondents) and dark gums (1 respondent). Meanwhile, chronic toxicity symptoms recorded include somatosensory disorders in gold processing workers. The majority of workers experience hearing loss (18 respondents), irritability (5 respondents), and headaches (3 respondents).